Analisa Kerasionalan Resep Pediatri Penderita Asma - Martha Dillia Handayani; Happy Elda Murdiana (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Asthma is an inflammatory disease characterized airways bronchoconstriction, inflammation, and excessive response to stimuli in addition, there are also inhibitory to air flow due to constriction of the bronchi. Resulting in hyperinflation distal lung mechanical changes, and increasing difficulty in breathing. Many factors that increase the severity of asthma include cigarette smoke, allergic rhinitis, sensitivity to aspirin.Objektive: to determine the classes of drugs and rational drug to patients who suffer from asthma in pediatric inpatient Panti Rapih Yogyakarta in January – December 2013.Methode: The method in this research is descriptive with cross sectional. Population in this study were all patient medical records in pediatric inpatient Panti Rapih Yogyakarta in January – December 2013. Samples in this study were all medical records of cases of asthma in pediatric inpatients aged 1 – 12 years in Panti rapih Yogyakarta in January – December 2013. Instrument used is the data collection sheet using non descriptive analytic classes of drugs include corticosteroids, β2 adrenergic, anticholinergic, rational drug with indication and appropriate mode of administration.Result: The treatment of most cases of asthma using β2 adrenergic much as 83 (79,8%), as many as 57 (54,8%) corticosteroids, anticolinergics as many as 8 (7,4%) and rationalization for indications and proper way of giving the results showed that all ratioal.Conclusion: The pattern of prescribing for pediatric asthma patients in inpatient Panti Rapih Yoyakarta is rationalKey words: Pediatric Asthma, Rational Prescription